Redistributive policy, inequality and growth - Hans Peter Grüner (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
Does redistribution increase inequality? Is inequality harmfiil for growth? Both questions have recently been addressed in a number of single-tax models. In this paper, I examine the relationship between policy, growth and inequality when income and wealth can be taxed at different rates. In the model, parents accumulate human and physical capital in order to increase the quality of their children. Inequality arises because the learning ability of children is stochastic. Redistributive labor income taxation has a negative impact on short- and long-run growth and inequality while capital taxation increases growth without reducing inequality. I calculate a structure-induced equilibrium of the political process by means of a stochastic Simulation of the model. In the short run initial income-inequality can stimulate growth, while initial inequality of the endowment with human capital is harmfiil for growth. In the long run the economies converge to the same politico-economic equilibrium.
Keywords: D31; H20; O15; O40; 330; Income distribution; endogenous growth; inheritance taxation; tax-policy